Enhancing Kiln Reliability in Cement Industry Using RCM II and FMEA - Faizzah, Mustika Ratnawati; Muti, Asri Amalia; HarisTanti, Sindy Nindia Maretha (Universitas Mercu Buana, 2025)
This study applies to the Reliability-Centered Maintenance (RCM) II methodology to improve the reliability and cost efficiency of a kiln system in a cement manufacturing plant. Kiln failures are critical because they cause unplanned downtime, reduced productivity, and financial losses. Traditional corrective or time-based maintenance strategies often fail to address the stochastic nature of failures in such high-temperature rotary systems. To overcome this gap, the research integrates Failure Mode and Effect Analysis (FMEA) with RCM II decision logic to identify and prioritize maintenance actions. The analysis focused on five critical kiln components—crusher cooler, firebrick lining, thrust roller, grate cooler, and main drive—using 12 months of operational data supported by expert interviews and technical manuals. Reliability indicators, including Mean Time to Failure (MTTF), Mean Time to Repair (MTTR), and Mean Time Between Failures (MTBF), were calculated, while Risk Priority Numbers (RPN) were assigned to rank failure modes. Results showed that the crusher cooler had the highest risk, whereas the main drive required the longest repair duration. Implementation of RCM II recommendations increased MTBF by 29–38% across components and reduced maintenance costs by more than 50%. These findings confirm that RCM II provides a practical, data-driven framework for enhancing system availability. The study contributes to maintenance engineering by demonstrating a structured approach that supports risk-informed and condition-based maintenance strategies in continuous-process industries.